Promising Practices in Coaching Co-taught Preservice Clinical Experiences - Toni S. Strieker; Woong Lim; David Rosengrant; Marcia Wright (Athens Journal of Education, 2020)
In 2010, the National Council for Accreditation of Teacher Education (NCATE) called for colleges and universities to "turn teacher education upside down" (pg. 2) and focus on clinical experiences, rather than coursework. This charge resulted in major shifts in teacher education programs in the USA as colleges and universities forged new partnerships to create yearlong clinical experiences that included co-teaching and coaching. In 2018, the American Association of Colleges for Teacher Education (AACTE) Commission on Clinical Experiences recognized and described the mutual benefits of expanding these partnerships between schools and universities to include various forms of collaboration, co-teaching and coaching. While these partnerships are increasing in number, little is known about the efficacy of the specific coaching approaches and practices employed in the co-taught classroom. This self-study examined the communication and behavioral approaches of 13 co-teaching coaches who collaborated with 39 teacher candidates enrolled in yearlong, co-taught P-12 clinical experiences. The co-teaching coaches attended up to four sessions of professional learning on co-teaching and coaching. Basic statistics were used to determine the demographics, the content of the coaching conversations, and preferred coaching approaches. The main data sources were the coaches’ resumes, their reflections on goal-setting sessions, observation reports, and surveys on their daily coaching activities. Results indicated that effective coaches engaged in collaborative dialogue that moved candidates to self-directed learning. Similarly, these results described the pedagogical practices of effective coaches in terms of goal-setting with the candidates, basic mentoring, and demonstration teaching.